Higher fibrinogen-to-albumin ratio is associated with the severity of toxin associated acute kidney injury in high-altitude (3650 m) population: A retrospective analysis - Wenling Yang; Lixia Cui; Yan He; Yong A; Jianbin Zhang; Quzhen Suolang; Luobu Ciren; Lei Zhang (PLoS ONE, 2026)
Background Few reports used acute kidney injury concept in the area of toxic kidney damage, especially in highland areas. Recent evidence suggests that the fibrinogen-to-albumin ratio is significantly associated with the incidence and severity of acute kidney injury, highlighting its potential clinical utility for risk stratification and prognostication in high-risk populations. We investigated the clinical characteristics and risk factors of toxic kidney injury in highland areas using the acute kidney injury criteria defined by the kidney disease improving global outcomes work group, with focus on the significance of the fibrinogen- to- albumin ratio. Methods Clinical data of poisoned patients who had electronic inpatient medical records during the past ten years were retrospectively analyzed, and risk factors affecting renal function were investigated. Results Sixty-five inpatients fulfill the criteria with the median age of 36.7 years old, including 40 females (61.5%). Thirty-four patients (52.3%) underwent blood purification, mainly hemoperfusion (n = 33). Medicine poisoning accounts for 53.8% (n = 35), including antipsychotic sedatives (n = 14) and Tibetan medicine (n = 9). Pesticide poisoning ranks the second (27.7%, n = 18). And the last was toxic substances eaten as food (n = 12). Among them, 39 cases (60.0%) were attributed to intentional self-poisoning. Multivariate linear regression analysis revealed that the serum creatinine concentration was positively related to the fibrinogen-to-albumin ratio, and to the concentrations of uric acid and serum phosphate: The reciprocal of the highest serum creatinine concentration (µmol/L) = 0.032–0.002 * uric acid concentration (µmol/L)/ 100 - 0.005 * serum phosphate concentration (mmol/L) −0.078 * the fibrinogen-to-albumin ratio + ε. The study demonstrated a dose-dependent association between elevated fibrinogen-to-albumin ratio and increased serum creatinine levels. Conclusions The public needs to be well informed to minimize the chance of exposure to excessive medicine, wild vegetables, toxic mushrooms, and pesticides. Traditional Tibetan medicine, unique to this plateau region, requires professional guidance for its identification, processing, and dosage. Mental well-being in plateau areas must be prioritized, and regulatory oversight of pesticides and antipsychotic sedatives need to be strengthened to mitigate the risks of overdose and toxic exposure. The serum creatinine concentration in poisoned patients in plateau regions may be affected by the fibrinogen-to-albumin ratio. Therapy against microinflammation, higher uric acid and phosphate levels may prevent further kidney injury.